Characterizing student engagement with hands-on, problem-based, and lecture activities in an introductory college course - Erickson, MaryGrace; Marks, Danielle; Karcher, Elizabeth (Teaching and Learning Inquiry, 2020)
This study examines the interest, motivation, and behavioral engagement of college students in an introductory course relative to three instructional formats used in the course: hands-on, problem-based laboratory stations; problem-based written case studies; and video lectures. Groups of five to seven students were assigned learning activities as treatments in a Latin Square design consisting of three experimental periods. At the beginning of selected laboratory sessions, students completed 10 minutes of the experimental activity immediately followed by a questionnaire. Students rated hands-on, problem-based laboratory stations as more challenging, novel, and attention-grabbing than they rated case studies or video lectures. Interest, intrinsic motivation, and behavioral engagement were greatest for groups completing laboratory stations followed by those completing case studies and lectures, respectively. Overall, the greater situational interest experienced during laboratory stations and case studies indicates that these activities can be leveraged to create learning environments that promote interest, engagement, and achievement.